Effects of Exposure to Microwaves: Problems and Perspectives - Michaelson, Sol M. (1974)
During the last 25 years, there has been a remarkable development and increase in the number of processes and devices that utilize or emit microwaves. Such devices are used in all sectors of our society for military, industrial, telecommunications, and consumer applications. Although there is information on biologic effects and potential hazard to man from exposure to microwaves, considerable confusion and misinformation has permeated not only the public press but also some scientific and technical publications. The purpose of this review is to place the available information on biologic effects of microwaves in proper perspective and to suggest approaches to future studies.